In Vitro and in Vivo Hypolipidemic Effects of Protein-Polysaccharide Complexes from Three Species of Edible Fungi - GAO Chen, LI Wen, CHEN Wanchao, WU Di, ZHANG Zhong, LIU Peng, XIA Yongjun, YANG Yan (Shipin Kexue)
Protein-polysaccharide complexes of Agaricus bisporus, Stropharia rugosa and Morchella esculenta were prepared and their protein and polysaccharide contents as well as amino acid and monosaccharide composition were evaluated. The in vitro and in vivo lipid-lowering effects of the complexes on oleic acid-induced liver LO-2 cells and high-fat diet fed mice were investigated. The results showed that the protein contents of the three complexes were (55.56 ± 0.51)%, (52.41 ± 0.31)%, and (54.96 ± 0.47)%, respectively, and the polysaccharide contents were (21.98 ± 1.17)%, (31.95 ± 0.52)%, and (15.55 ± 0.78)%, respectively. In vitro cell experiments showed that all the complexes significantly inhibited the accumulation of lipid droplets in hepatocytes. Animal experiments showed that they significantly inhibited the increase in body mass, triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) levels, blocked the swelling of the swelling of hepatocytes, and inhibited hepatic lipid deposition in mice fed a high-fat diet. In the high-dose group, the hepatic lipid content of mice with hyperlipidemia was reduced from (30.59 ± 0.38)% to (13.74 ± 1.57)%, (9.68 ± 0.73)%, and (7.15 ± 0.39)%, respectively, by the complexes from A. bisporus, S. rugosa and M. esculenta, and the inhibition rates of hepatic lipid droplets by these complexes were (55.09 ± 5.12)%, (68.34 ± 2.37)% and (76.64 ± 1.28)%, respectively. In addition, the protein-polysaccharide complexes alleviated liver function damage caused by long-term high-fat diet. In summary, it can be concluded that A. bisporus, S. rugosa and M. esculenta protein-polysaccharide complexes can regulate lipid metabolism, alleviate liver injury and hyperlipidemia, which provides a reference for the development of functional products based on edible fungi.